2018
DOI: 10.1186/s12877-018-0991-0
|View full text |Cite
|
Sign up to set email alerts
|

Hand grip strength as a physical biomarker of aging from the perspective of a Fibonacci mathematical modeling

Abstract: BackgroundThe Golden Ratio (GR) and the Fibonacci sequence have wide applications in biodiversity research, and recent studies indicate that the GR can be highlighted in the organization and physiological functioning of many body systems. The aim of this cross-sectional descriptive study is to determine the applicability of a mathematical model derived from the Fibonacci sequence to investigate the changes in hand grip strength (HGS) induced by the aging process.MethodsWe assessed the HGS for both hands, using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
(51 reference statements)
0
21
0
2
Order By: Relevance
“…Several authors have recommended grip strength as a "useful indicator for overall health," 16 a vital sign 4,5 and as a biomarker of health status. 3,138,139 The purpose of this literature review was to provide an up-to-date, thorough and balanced synopsis of evidence for using grip strength as a biomarker of current and future health status. Based on the review it appears that there is adequate evidence to support the use of grip strength as an explanatory or predictive biomarker of specific outcomes such as generalized strength and function, bone mineral density, fractures, and falls, nutritional status, disease status and comorbidity load, cognition, depression, and sleep, hospital-related variables, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have recommended grip strength as a "useful indicator for overall health," 16 a vital sign 4,5 and as a biomarker of health status. 3,138,139 The purpose of this literature review was to provide an up-to-date, thorough and balanced synopsis of evidence for using grip strength as a biomarker of current and future health status. Based on the review it appears that there is adequate evidence to support the use of grip strength as an explanatory or predictive biomarker of specific outcomes such as generalized strength and function, bone mineral density, fractures, and falls, nutritional status, disease status and comorbidity load, cognition, depression, and sleep, hospital-related variables, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, hand grip strength (HGS) has wide usefulness for the standardized determination of the individual's health and level of functionality, the impact of morbidity/disability, or the appreciation of the dynamics of the aging process [30]. In a recent study, we also demonstrated the applicability of HGS as a parameter for mathematical modeling for the study of the process of aging [31].…”
Section: Applications Of Poincaré Plot In the Analysis Of The Biologimentioning
confidence: 99%
“…Recent researches have been reports that the transmission of vibratory stimuli throughout responses which depend on the proprieties of these stimuli. Vibration generated by a platform and transmitted to the body, activates a series of sensory receptors, from cutaneous to muscular [11].…”
Section: Vibrotherapy For Stimulating the Muscle Strength And Rehabilmentioning
confidence: 99%